Internet gaming disorder dan penyesuaian sosial remaja - Riyana, Meli; Hasan, Nur; Soelistyowati, Niken (PSYCOMEDIA : Jurnal Psikologi, 2023)
This study aims to determine the relationship between internet gaming disorders and social adjustment in adolescents. This study uses a quantitative approach with a correlational research design. There were 70 participants in this study who were obtained through a convenience sampling technique. This research was conducted online using Google Forms. The data analysis technique was performed using Pearson's correlation. The Pearson correlation test results show that there is a negative and significant correlation between internet gaming disorder and social adjustment in adolescents. These results indicate that an increase in internet gaming disorders will cause a decrease in social adjustment abilities in adolescents.